2016
DOI: 10.1109/tit.2016.2530398
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Function Computation Over a Rooted Directed Tree

Abstract: This paper establishes the rate region for a class of source coding function computation setups where sources of information are available at the nodes of a tree and where a function of these sources must be computed at the root.The rate region holds for any function as long as the sources' joint distribution satisfies a certain Markov criterion.This criterion is met, in particular, when the sources are independent.This result recovers the rate regions of several function computation setups. These include the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…In [6], the function computation rate is defined and lower bounds on such rate are obtained for various simple classes of functions. Recently, in [65], informationtheoretic bounds on the function computation rate were ob- tained for a special case, when network is a directed rooted tree, and the set of sinks contains only the root of the tree, and the source symbols satisfy a certain Markov criterion. A number of works study computation of sum in the network.…”
Section: A Theoretical Aspects Of Nfc Layermentioning
confidence: 99%
“…In [6], the function computation rate is defined and lower bounds on such rate are obtained for various simple classes of functions. Recently, in [65], informationtheoretic bounds on the function computation rate were ob- tained for a special case, when network is a directed rooted tree, and the set of sinks contains only the root of the tree, and the source symbols satisfy a certain Markov criterion. A number of works study computation of sum in the network.…”
Section: A Theoretical Aspects Of Nfc Layermentioning
confidence: 99%
“…In the case of lossless (in the Shannon sense) computation, it was shown that the minimum average rate is the conditional graph entropy of the characteristic graph of the source [17], [18]. Building upon this line of research, the rate region for the lossless DFC problem was characterized for certain problem instances [14], [15]. Sefidgaran et al.…”
Section: A Non-interactive Communication: Fundamental Limitsmentioning
confidence: 99%
“…In the case of lossless (in the Shannon sense) computation, it was shown that the minimum average rate is the conditional graph entropy of the characteristic graph of the source [17], [18]. Building upon this line of research, the rate region for the lossless DFC problem was characterized for certain problem instances [14], [15]. Sefidgaran et al derived inner and outer bounds to the rate region for a class of tree-structured networks (which includes the CEO problem) and showed that the inner and outer bound coincide with each other if the sources obey certain Markov properties [14].…”
Section: A Non-interactive Communication: Fundamental Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also gave an inner bound to the rate region of a general tree network. The rate region for a multi-stage tree-network when every source message at a vertex in the network satisfies a local Markovian property was characterized in [44]. The function computation scenarios described above all allowed for a vanishing block-error probability with asymptotically large block lengths.…”
Section: Introductionmentioning
confidence: 99%